Situating organisational learning and public participation: Stories, spaces and connections. Issue 2 (26th September 2017) - Pallett, Helen
Abstract : This paper gives one of the first in‐depth ethnographic accounts of organisational learning in a public participation organisation, the UK Government‐funded Sciencewise programme. It develops the concept of "organisational spaces", highlighting the often diverse spaces found within organisational networks, and positing a co‐productionist relationship between these different spaces and the kinds of learning processes that occur. The approach taken affirms the significant and active role of space in organisational learning processes, in a science policy context, as well as demonstrating the importance of connections between different organisational spaces in enabling more transformative learning processes. Two organisational spaces are described based on in‐depth ethnographic and qualitative research in and around the Sciencewise programme 2013–2014. It is argued that informal, temporary and experimental organisational spaces have the potential to co‐produce more transformative instances of learning, making an understanding of their connectedness to more formal and routinised organisational spaces vital for future research.